Sintesis N-p-Metilbenzil-p-Kumaramida dari Asam p-Kumarat - Nasriadi Dali; Arniah Dali (Al-Kimia, 2017)
N-p-Methylbenzyl-p-coumaramide has been synthesized from p-coumaric acid. The purpose of this study was to synthesize N-p-methylbenzyl-p-coumaramide compounds from p-coumaric acid. The N-p-methylbenzyl-p-coumaramide target compound was obtained by direct conversion method using a orthoboric acid catalyst. Target compounds were identified and characterized by melting point, TLC test, FTIR, 1H-NMR, and 13C-NMR spectrometer. The results showed that N-p-methylbenzyl-p-coumaramide compound obtained was white solid (yield 75.83%) with melting point 156-158 oC and TLC (SiO2, n-hexane : chloroform = 5: 3 v/v, Rf = 0.37).